Strengthening multi-sectoral participation in watershed management the case of the Wawa watershed in Sitio Wawa, Barangay San Rafael, Rodriguez, Rizal - Plaza, Aldrin B (2007)
This study looks into how multi-sectoral participation can effectively play a role in the formulation of management strategies and on on-site administration of the Wawa Watershed.
"October 2007."
Thesis (M.A. Urban & Regional Planning)--University of the Philippines Diliman.
Keywords: Watershed management -- Philippines -- Rodriguez (Rizal).